Facing Forward. Art and Theory from a Future Perspective - Schavemaker, Margriet; Folkerts, Hendrik; Lindner, Cristoph (Amsterdam University Press, 2015)
This spirited exploration of the interfaces between art and theory in the 21st century brings together a multidisciplinary range of viewpoints on their future. The authors examine contemporary visual culture based on speculative predictions and creative scientific arguments. Focusing on seven themes - Future Tech, Future Image, Future Museum, Future City, Future Freedom, Future History, and Future Future - the book shows how our sense of the future is shaped by a visual rhetoric of acceleration, progression, excess and destruction. The essays reflect collaborative work between the Stedelijk Museum Amsterdam, the Amsterdam School for Cultural Analysis at the University of Amsterdam, De Appel Arts Centre, W139-Space for Contemporary Art, and the art magazine Metropolis M. Discussing provocative themes like future history and future freedom, 'Facing Forward' is an energetic look at how our visions of the future affect how we depict the world around us.